PENGARUH PENDAPATAN, LUAS LAHAN, LOKASI LAHAN DAN JENIS PEKERJAAN TERHADAP KEPUTUSAN MASYARAKAT MENGKONVERSI LAHAN PERTANIAN MENJADI LAHAN NON-PERTANIAN - ANISA RAMITAYUDHA (PPJP Universitas Lambung Mangkurat, 2018)
This research aims to determine whether income, land area, land location and the type of work to people’s have significant effect simultaneously and partially to the people's decision to convert agricultural land into non-agricultural land in Gambut Sub-District, and to know its impact on the welfare of the land owners.This research is a quantitative research, using primary data in the form of interviews with 80 communities that have agricultural land in Gambut Sub-District in 2016 until 2017.The result of logit model regression shows that all variables have significant effect simultaneously to people's decision to convert agricultural land into non-agricultural land in Gambut Sub-District, whereas only partially significant influence is income and land area, where income and land area have negative relation with conversion rate of agricultural land. Different test results show that there is a marked difference between the income of the community before and after converting agricultural land. Average community income before converting agricultural land is greater than after converting agricultural land.Keywords: Agricultural Land, Conversion, Income, Land Area, People’s Welfare